Modulation of Regulatory T Cells Activity by Distinct CD80 and CD86 Interactions With CD28/CTLA-4 in Chagas Cardiomyopathy - Pinto, Bruna F.; Medeiros, Nayara I.; Teixeira-Carvalho, Andrea; Fiuza, Jacqueline A.; Eloi-Santos, Silvana M.; Nunes, Maria C. P.; Silva, Silvana A.; Fontes-Cal, Tereza C. M.; Belchior-Bezerra, Mayara; Dutra, Walderez O.; Correa-Oliveira, Rodrigo; Gomes, Juliana A. S. (Frontiers in Cardiovascular Medicine, 2022)
Chagas cardiomyopathy is the symptomatic cardiac clinical form (CARD) of the chronic phase of Chagas disease caused by Trypanosoma cruzi infection. It was described as the most fibrosing cardiomyopathies, affecting approximately 30% of patients during the chronic phase. Other less frequent symptomatic clinical forms have also been described. However, most patients who progress to the chronic form develop the indeterminate clinical form (IND), may remain asymptomatic for life, or develop some cardiac damage. Some mechanisms involved in the etiology of the clinical forms of Chagas disease have been investigated. To characterize the contribution of CD80 and CD86 co-stimulatory molecules in the activation of different CD4+ (Th1, Th2, Th17, and Treg) and CD8+ T lymphocyte subsets, we used blocking antibodies for CD80 and CD86 receptors of peripheral blood mononuclear cells (PBMC) in cultures with T. cruzi antigens from non-infected (NI), IND, and CARD individuals. We demonstrated a higher frequency of CD8+ CD25+ T lymphocytes and CD8+ Treg cells after anti-CD80 antibody blockade only in the CARD group. In contrast, a lower frequency of CD4+ Treg lymphocytes after anti-CD86 antibody blockade was found only in IND patients. A higher frequency of CD4+ Treg CD28+ lymphocytes, as well as an association between CD4+ Treg lymphocytes and CD28+ expression on CD4+ Treg cells in the CARD group, but not in IND patients, and once again only after anti-CD80 antibody blockade, was observed. We proposed that Treg cells from IND patients could be activated via CD86-CTLA-4 interaction, leading to modulation of the immune response only in asymptomatic patients with Chagas disease, while CD80 may be involved in the proliferation control of T CD8+ lymphocytes, as also in the modulation of regulatory cell activation via CD28 receptor. For the first time, our data highlight the role of CD80 in modulation of Treg lymphocytes activation in patients with CARD, highlighting a key molecule in the development of Chagas cardiomyopathy.